Зміни чутливості до інсуліну в патогенезі дифузного токсичного зоба - Ліщук, О. З.; Кіхтяк, О. П.; Москва, Х. А.; Ліщук, Б. Ф. (Clinical Endocrinology and Endocrine Surgery, 2014)
Recently reports on disturbances of insulin sensitivity in the diseases of the thyroid gland have become frequent. Though insulin resistance is traditionally considered the cause of diabetes mellitus type 2, polycystic ovary syndrome, arterial hypertension, Cushing syndrome and acromegaly in the last decades it has been found that disturbances of receptor and post receptor insulin interaction develop in diffusive toxic goiter. The paper presents data on laboratory markers that prove the presence of peripheral sensitivity to insulin in patients with diffuse toxic goiter and results of using medications in correction of insulin resistance with insulin sensitizers (metformin, pioglitazone) based on main antithyroid therapy. The results of our investigation show the increased indices of HOMA-IR and HOMA-b, the level of low-density lipoproteins and concentration of triglycerides in patients with diffuse toxic goiter after one month treatment with thiamazole.